Perancangan Aplikasi Sistem Informasi Sumsel Tourism Berbasis Android - Febby Ayu Permatasari; Ali Nurdin; Jon Endri (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2019)
The increase in the number of tourists to South Sumatra can be seen from the interest of visitors who come to the area for tourist destinations. The tourists from outside of South Sumatra who have visited this province for the first time will have difficulty accessing detailed information on tourist place and lodging. So, South Sumatra should be able to develop facilities regarding tourist directions to facilitate tourists. The purpose of this research presents an application to help users find information about tourist place and lodging then make users easier to book tourist place. The development of application made using the waterfall method and the Java, PHP, XML programming language with Android Studio 181.5 software. Then the concept used is the Unified Modeling Language (UML) with Activity Diagrams. The results of this research are android-based by online application that can display information in the form of profiles, contacts, budget, routes to the location of tourist places and lodging places then make the tourist easier to book tourist places.